2019
DOI: 10.1002/wsb.971
|View full text |Cite
|
Sign up to set email alerts
|

Less invasive monitoring of cougars in Colorado's front range

Abstract: From 2014 to 2016, in the Front Range of Colorado, USA, we assessed noninvasive approaches to sampling cougar (Puma concolor) populations in an attempt to provide a new method that would be less field intensive, less expensive, and could be applied over large spatial extents compared with current methods. We assessed the use of predator calls to lure cougars to a site with remote camera traps for detection and also evaluated hair snags at sites to noninvasively identify individual animals. Predator calls effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
12
2
Order By: Relevance
“…Thus, in non‐surveyed areas managed for puma conservation and sustainable hunting, managers should apply conservative density assumptions and harvest rates to improve the odds of successful management. When resources allow for rigorous monitoring, puma abundance could be estimated over time using newly developed genetic sampling and photographic mark‐recapture methods in representative management units (e.g., Proffitt et al 2015, Beausoleil et al 2016, Alldredge et al 2019, Murphy et al 2019).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Thus, in non‐surveyed areas managed for puma conservation and sustainable hunting, managers should apply conservative density assumptions and harvest rates to improve the odds of successful management. When resources allow for rigorous monitoring, puma abundance could be estimated over time using newly developed genetic sampling and photographic mark‐recapture methods in representative management units (e.g., Proffitt et al 2015, Beausoleil et al 2016, Alldredge et al 2019, Murphy et al 2019).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Cougar population density in this area was estimated at 4.1 independent cougars per 100 km 2 , one of the highest reported cougar densities in the literature (Alldredge, Blecha, & Lewis, 2019), indicating that cougars are likely doing very well in these urban habitats. Similar patterns of high carnivore density and human conflict in urban areas have been documented for leopard (Panthera pardus) and striped hyena (Hyaena hayena) (Athreya, Odden, Linnell, Krishnaswamy, & Karanth, 2013), suggesting the adaptability of carnivores may generally allow them to exploit urban environments despite human conflict and increased risk of mortality.…”
Section: Discussionmentioning
confidence: 64%
“…Because wildland and rural habitat are combined, it may be that these areas provide fewer prey resources, especially during the winter, compared with exurban habitat. It is possible that this may be an artifact of lower sampling effort in the western portion of the study area as capture efforts focused more on the exurban eastern edge, but a concurrent study estimating cougar density in this study area suggested a similar distribution of cougars (Alldredge et al, ). Regardless, the avoidance of housing was still predictable showing cougar avoidance of humans when in more rural and open areas, and avoidance of suburban and urban areas.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, we did not assume demographic or geographic closure because recruitment, mortality, and emigration were accounted for. Collectively, the advantages of our method include accurate determination of space use and an identifiable proportional density for specific demographic classes, but we acknowledge this undertaking may be cost‐prohibitive (Alldredge et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cougar density is derived primarily using 3 techniques: population abundance divided by a generalized study area (Choate et al 2006, Lambert et al 2006, Robinson and DeSimone 2011), using global positioning systems (GPS) locations and demographic data from collared cougars to define specific sex and age class contributions within a defined study area (Cooley et al 2009, Rinehart et al 2014, this study), and spatially explicit capture‐recapture (SECR; Russell et al 2012, Robinson et al 2014, Proffitt et al 2015). Other estimates of abundance may be derived from population reconstruction of hunter‐harvest data (Howard et al 2020) or indexing density using a reciprocal of female home ranges (Stoner et al 2018); time‐to‐detection (Loonam et al 2021) and modified mark‐resight (Alldredge et al 2019, Murphy et al 2019) models represent viable alternatives that are becoming more common. Each approach can provide robust or beneficial estimates, but the inconsistency between methodologies and definitions impede direct comparison of results.…”
mentioning
confidence: 99%